Description of the second known specimen of Apostolepis intermedia (Serpentes, Colubridae, Xenodontinae) - de Albuquerque, Nelson Rufino; de Lema, Thales (Zootaxa, 2012)
Apostolepis intermedia is a xenodontine colubrid snake known only from the lost holotype described in 1898 from Miran-da, Mato Grosso do Sul. Here, we describe a second specimen collected in 1997 on the margins of Taquaruçu river, Anas-tácio ca. 66.2 km from Miranda. We present photographs and drawings of the specimen and compare it with the original description of the holotype and 11 other five-lined congeners.